2013
DOI: 10.1155/2013/183713
|View full text |Cite
|
Sign up to set email alerts
|

Investigations into Deformation Characteristics during Open-Die Forging of SiCp Reinforced Aluminium Metal Matrix Composites

Abstract: The deformation characteristics during open-die forging of silicon carbide particulate reinforced aluminium metal matrix composites (SiC AMC) at cold conditions are investigated. The material was fabricated by liquid stir casting method in which preheated SiC particles were mixed with molten LM6 aluminium casting alloy and casted in the silicon mould. Finally, preforms obtained were machined in required dimensions. Two separate cases of deformation, that is, open-die forging of solid disc and solid rectangular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Aluminium matrix composites (AMC) are synergic materials having high specific strength, high specific modulus, high wear resistance and improved high temperature properties [1][2] . They are the potential materials to replace metals and alloys in weight critical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Aluminium matrix composites (AMC) are synergic materials having high specific strength, high specific modulus, high wear resistance and improved high temperature properties [1][2] . They are the potential materials to replace metals and alloys in weight critical applications.…”
Section: Introductionmentioning
confidence: 99%
“…As specified here DEFORM-3D software to do finite element analysis to find the Forging Properties of material [1]. This tool has a material library with the properties and allow user to change as per the requirement.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that strength property is very high at 5% of SiC with copper and the initiation of crack appeared at a low axial strain with higher value of SiC addition. Verma et al (2013) have investigated the deformation characteristics during open-die forging of silicon carbide particulate reinforced aluminium metal matrix composites (Si-Cp AMC) at cold conditions. Authors have not yet come across the investigations in which the effect of strain rate (based on ram velocity) on the composite preform has been taken into consideration, as the strain rate is one of the most important parameter in forging process.…”
Section: Introductionmentioning
confidence: 99%